IMPROVING COMMUNICATION AND LISTENING COMPREHENSION SKILLS IN ENGLISH THROUGH INTERACTIVE EXERCISES (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The article analyzes the pedagogical significance and effectiveness of developing communication and listening comprehension skills in English through interactive exercises. Group work, pair work, role plays, problemsolving tasks, and audio materials significantly improve students’ practical speaking and listening skills. The study demonstrates the effectiveness of interactive methods in a polytechnic context.